2023
DOI: 10.1200/jco.22.02018
|View full text |Cite
|
Sign up to set email alerts
|

Initial Evidence for the Efficacy of Naporafenib in Combination With Trametinib in NRAS-Mutant Melanoma: Results From the Expansion Arm of a Phase Ib, Open-Label Study

Abstract: PURPOSE No approved targeted therapy for the treatment of patients with neuroblastoma RAS viral (v-ras) oncogene homolog ( NRAS)–mutant melanoma is currently available. PATIENTS AND METHODS In this phase Ib escalation/expansion study (ClinicalTrials.gov identifier: NCT02974725 ), the safety, tolerability, and preliminary antitumor activity of naporafenib (LXH254), a BRAF/CRAF protein kinases inhibitor, were explored in combination with trametinib in patients with advanced/metastatic KRAS- or BRAF-mutant non–sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…7, A to F). Notably, the sorafenib/trametinib combination has already been applied in the context of BRAF class III mutations ( 83 ) and advanced hepatocellular carcinoma ( 84 ), while first clinical data on naporafenib/trametinib combinations have recently been published for NRAS-driven melanoma ( 85 ). We also tested whether the efficacy of naporafenib could be further improved by the HSP90i XL888, which shows clinical activity in combination with vemurafenib in melanoma ( 49 , 86 ).…”
Section: Resultsmentioning
confidence: 99%
“…7, A to F). Notably, the sorafenib/trametinib combination has already been applied in the context of BRAF class III mutations ( 83 ) and advanced hepatocellular carcinoma ( 84 ), while first clinical data on naporafenib/trametinib combinations have recently been published for NRAS-driven melanoma ( 85 ). We also tested whether the efficacy of naporafenib could be further improved by the HSP90i XL888, which shows clinical activity in combination with vemurafenib in melanoma ( 49 , 86 ).…”
Section: Resultsmentioning
confidence: 99%
“…31 Similar findings were seen in other Ras-mutant tumors when the BRAF/CRAF inhibitor naporafenib was combined with the MEKi trametinib. 32 In the phase Ib study of naporafenib + trametinib, reported here by de Braud et al, 8 the evidence of antitumor activity was seen in > 46% of patients with heavily pretreated NRAS-mutant melanoma. These encouraging findings suggest that targeted therapies could be developed for NRAS-mutant melanoma.…”
mentioning
confidence: 85%
“…Ras proteins have proven difficult to target, and although inhibitors of KRAS have recently been developed with promising clinical activity reported, 5-7 equivalent inhibitors of mutant NRAS are lacking. In the accompanying article, de Braud et al 8 report encouraging results from the expansion arm of a phase Ib dose escalation trial of the BRAF/CRAF kinase inhibitor naporafenib (LXH254) in combination with the MEK inhibitor trametinib in NRAS-mutant melanoma. In this understanding the pathway article, we review the biology of mutant NRAS in melanoma and discuss strategies for targeting this pathway.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As such, the discovery of pan-RAF inhibitors that can block RAF dimer-dependent signaling has received significant attention from the scientific community . Naporafenib ( 3 ) and belvarafenib ( 4 ) are clinical stage inhibitors that have shown promising preclinical activity against RAF homo- and heterodimers, and both inhibitors are currently advancing in the clinic in combination with MEK inhibitors in patients harboring NRAS-driven cancers. , However, both compounds carry challenging physical and chemical properties that may constrain their effectiveness for robust alteration coverage as monotherapy. For example, the low thermodynamic solubility of compound 3 required a thermomechanical solid dispersion formulation to improve oral bioavailability…”
Section: Introductionmentioning
confidence: 99%